GAMBARAN STATUS KEBERSIHAN GIGI DAN MULUT PADA KOMUNITAS ANAK JALANAN TANPA BATAS DI KOTA X (Jurnal Kesehatan Siliwangi, 2020)
Street children are the children who spend most of their time doing activities that are daily living on the streets, whether for a life or just wandering around other public areas. Usually the age of street children between 5 years to 18 years, the appearance is dull and look unmanaged, causing a lack of attention to the cleanliness of the tooth and mouth. This type of research is descriptive, the respondent that is taken is the whole team and the Of Street Children’s Community Without Border Bandung. The of Samples taken as much as 16 people obtained data is presented in the form of frequency distribution table. The result showed that the result of an OHI-S index of 9 people (55%) Those have good criteria (OHI-S), and 7 responden 45%) have moderate criteria. This Index should be maintained and would be better if improved from being good, it is influenced by the lack of information/education, understanding and awareness of each respondent. Keyword: Street children, dental hygiene and mouth